Effects of Iron Isomaltoside vs Ferric Carboxymaltose on Hypophosphatemia in Iron-Deficiency Anemia: Two Randomized Clinical Trials - Wolf, Myles (JAMA, 2020)
IMPORTANCE: Intravenous iron enables rapid correction of iron-deficiency anemia, but certain formulations induce fibroblast growth factor 23–mediated hypophosphatemia. OBJECTIVE: To compare risks of hypophosphatemia and effects on biomarkers of mineral and bone homeostasis of intravenous iron isomaltoside (now known as ferric derisomaltose) vs ferric carboxymaltose. DESIGN, SETTING, AND PARTICIPANTS: Between October 2017 and June 2018, 245 patients aged 18 years and older with iron-deficiency anemia (hemoglobin level ≤11 g/dL; serum ferritin level ≤100 ng/mL) and intolerance or unresponsiveness to 1 month or more of oral iron were recruited from 30 outpatient clinic sites in the United States into 2 identically designed, open-label, randomized clinical trials. Patients with reduced kidney function were excluded. Serum phosphate and 12 additional biomarkers of mineral and bone homeostasis were measured on days 0, 1, 7, 8, 14, 21, and 35. The date of final follow-up was June 19, 2018, for trial A and May 29, 2018, for trial B. INTERVENTIONS: Intravenous administration of iron isomaltoside, 1000 mg, on day 0 or ferric carboxymaltose, 750 mg, infused on days 0 and 7. MAIN OUTCOMES AND MEASURES: The primary end point was the incidence of hypophosphatemia (serum phosphate level <2.0 mg/dL) between baseline and day 35. RESULTS: In trial A, 123 patients were randomized (mean [SD] age, 45.1 [11.0] years; 95.9% women), including 62 to iron isomaltoside and 61 to ferric carboxymaltose; 95.1% completed the trial. In trial B, 122 patients were randomized (mean [SD] age, 42.6 [12.2] years; 94.1% women), including 61 to iron isomaltoside and 61 to ferric carboxymaltose; 93.4% completed the trial. The incidence of hypophosphatemia was significantly lower following iron isomaltoside vs ferric carboxymaltose (trial A: 7.9% vs 75.0% [adjusted rate difference, –67.0% {95% CI, –77.4% to –51.5%}], P < .001; trial B: 8.1% vs 73.7% [adjusted rate difference, –65.8% {95% CI, –76.6% to –49.8%}], P < .001). Beyond hypophosphatemia and increased parathyroid hormone, the most common adverse drug reactions (No./total No.) were nausea (iron isomaltoside: 1/125; ferric carboxymaltose: 8/117) and headache (iron isomaltoside: 4/125; ferric carboxymaltose: 5/117). CONCLUSIONS AND RELEVANCE: In 2 randomized trials of patients with iron-deficiency anemia who were intolerant of or unresponsive to oral iron, iron isomaltoside (now called ferric derisomaltose), compared with ferric carboxymaltose, resulted in lower incidence of hypophosphatemia over 35 days. However, further research is needed to determine the clinical importance of this difference. TRIAL REGISTRATION: ClinicalTrials.gov Identifiers: NCT03238911 and NCT03237065